Integrating BCI with Virtual Reality - Galphat, Y; Gangwani, M; Bhave, A; Chadha, BS; Adnani, S (International Journal of Computer Sciences and Engineering, 2025)
The purpose of this project is to implement a VR game in which the EEG headset is trained to respond to the stimuli within the game by capturing a player’s EEG signals. These EEG signals are generated by the player’s emotions such as attention and meditation. Using the values obtained from the EEG headset we will enable the player to control the game using the headset. The main objective of this project is to empower a person with the ability to control any object in a virtual environment by analysing brain wave patterns and applying the resultant data to train the Brain Control Interface(BCI) device. The vision of the project is to make a player free from using hardware plug-ins and control the game using BCI.